Morphometric and Hypsometric Assessment of the Spna Watershed (Iraqi National Journal of Earth Science (INJES), 2026)
The study presents a comprehensive morphometric and hypsometric (HI) analysis and correlation of the Spna watershed, located about 50 km northwest of Duhok City. The watershed has an overall area of 317.65km2. Using a 12.5 m resolution Digital Elevation Model (DEM) and ArcGIS Pro, the basin was delineated and divided into 15 sub-watersheds. Three different morphometric parameters- relief, areal, and linear were quantitatively analyzed. Results show the watershed has a coarse drainage density (3.12 km/km²), a moderate bifurcation ratio (average 4.3), and an elongated shape, suggesting moderate surface runoff and susceptibility to erosion. The hypsometric curve analysis shows that the main watershed has an HI value of 0.28, which means it is in an older stage of landform development, while the result of HI in sub-watersheds varies from 0.24 to 0.47, showing they are at different stages from youthful to mature. There were high negative correlations between HI and watershed parameters, such as elevation, area, and ruggedness index. These indicate the effect of terrain morphology on erosion potential and stability.
Keywords: Morphometric, Hypsometric, Correlation, Spna.